2019
DOI: 10.1055/s-0039-1697653
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of the Every Second Matters for Mothers-Uterine Balloon Tamponade (ESM-UBT) Device: In Vitro Tests

Abstract: Objective  Postpartum hemorrhage (PPH) is the most common cause of maternal mortality and morbidity worldwide, most of which occurs in resource-poor settings. Placement of a uterine balloon may be life-saving in uncontrolled PPH. The Every Second Matters for Mothers-Uterine Balloon Tamponade (ESM-UBT) device is an ultra-low-cost uterine balloon designed for global access. The purpose of this study was to evaluate the mechanical properties of the ESM-UBT device. Study design  Intraluminal pressures, diameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 35 publications
1
27
3
Order By: Relevance
“…Finally, it is false that condoms explode after being filled with more than 250À300 mL. A recent in vitro study 5 concluded that intraluminal pressure of condoms remains stable with instillation of saline between 300 mL and 1200 mL, a volume that has also been reported in in vivo studies. Importantly, in this study, no condoms burst with volumes 5000 mL of saline.…”
Section: Replymentioning
confidence: 95%
“…Finally, it is false that condoms explode after being filled with more than 250À300 mL. A recent in vitro study 5 concluded that intraluminal pressure of condoms remains stable with instillation of saline between 300 mL and 1200 mL, a volume that has also been reported in in vivo studies. Importantly, in this study, no condoms burst with volumes 5000 mL of saline.…”
Section: Replymentioning
confidence: 95%
“…The Ministry of Health and Family Welfare, Government of India is assessing the most cost-effective UBT device for atonic PPH management in the public health system given the emerging evidence for relatively low cost ESM-UBT alternative. [19][20][21] The policy decision to make a UBT device available for PPH management across health facilities will have associated cost and health outcome implications. This study aimed to calculate public health system cost of atonic PPH management with SOC, that is, condom-UBT recommended by the 2015 Indian guidelines for PPH management with similar projections for ESM-UBT and another globally used Bakri-UBT device.…”
Section: Open Accessmentioning
confidence: 99%
“…To date, no before‐and‐after study has evaluated the impact of introducing UBT for the management of severe PPH in low‐ and/or middle‐income countries. Since commercial UBT devices are unaffordable in most resource‐limited settings, our team addressed this problem by developing the “Every Second Matters for Mothers and Babies‐Uterine Balloon Tamponade” (ESM‐UBT) device 18–22 . The ESM‐UBT device is an ultra‐low‐cost, high‐quality, US FDA approved, easy to use condom‐catheter UBT, which is as efficacious and safe as a Bakri balloon for treating PPH 14,23 …”
Section: Introductionmentioning
confidence: 99%
“…Since commercial UBT devices are unaffordable in most resource-limited settings, our team addressed this problem by developing the "Every Second Matters for Mothers and Babies-Uterine Balloon Tamponade" (ESM-UBT) device. [18][19][20][21][22] The ESM-UBT device is an ultra-low-cost, highquality, US FDA approved, easy to use condom-catheter UBT, which is as efficacious and safe as a Bakri balloon for treating PPH. 14,23 The aim of this study was to evaluate the impact of introducing the ESM-UBT device for managing severe PPH in health facilities in India on the rates of PPH-related maternal death and invasive procedures.…”
Section: Introductionmentioning
confidence: 99%